Estudo de verbos codificadores de extensão ou escala no jogo da linguagem : uma perspectiva funcionalista - Cristóvão, Heloá Ferreira (2013)
The most of grammarians welcome verbs in two sessions, namely: the first that deals with morphological aspects, then within a syntactic-semantic perspective, which deals with verbs as the predication. This creates the problem of proposal analysis, given that when considering verbs as discrete elements in non-contextualized sentences, the relationships are not considered morphological, syntactic, semantic, pragmatic and discoursive that can only be observed from the language in use, in game combinatorial language. From these considerations, the design language we adopt is consistent with that proposed by functionalism, which advocates the study of linguistic phenomena from the analysis of the structures in actual use, prioritizing the relationships established in the communicative context. Equally important was the study of argument structure of sentence, formed by the verb and its selected elements required (arguments). With respect to verbs that will be the object of research, we look to the classification performed by Azeredo (2004, p.180), based on the study proposal of Cano Aguilar (1981) for the Spanish language, that enrolled a group of verbs encoders of extent or scale in Portuguese, among them: cross, roam, rise, embrace, preside, contour, occupy, fill, flood, measure 1 (he measured a piece of land), measure 2 (the land measures 160 m), earn and last (the trip lasted 80 days). In our research, we analyze the transitivity of a clipping of this group, consisting of the verbs rise, occupy, measure, last, earn and their use in the Portuguese language, which, together with the choice of theoretical, justify the importance of this study, since this phenomenon is best observed in real communication. The corpus is composed of texts within the journalistic writing and data collection was conducted through a research tool on-line in digital collection of Veja Magazine. We hope that the result of this research it is clear that a study has as starting point the language used go far beyond the propositions of grammars